Are they even there? How agri-environment schemes investments reach their target species in Dutch dairy-farmland, the case of meadow birds - Barba-Escoto, Luis; Howison, Ruth Alison; Fokkema, Rienk W.; Duriaux-Chavarría, Jean-Yves; Stessens, Marie; Velde, Egbert van der; Hooijmeijer, Jos C.E.W.; Piersma, Theunis; Tittonell, Pablo Adrian (Elsevier, 2024)
Agri-environmental schemes (AES) implemented by farmer collectives for meadow bird protection in The Netherlands create complex landscape mosaics due to the variability of options and combinations farmers use. We propose a method to simplify this complexity, using the number of meadow birds potentially benefiting as the measure of success, and evaluate how AES combinations affect management success as a function of monetary investments. Between 2016 and 2022, we conducted field surveys to measure the density and distribution of Black-tailed Godwits across three land-use types: AES, site-protected areas, and intensive agriculture. AES fields were categorized into nest protection, inundation, delayed mowing, and herb-rich grasslands. We analysed the relationship between these managements, the area they cover, and godwit numbers, while also examining land area and subsidies. Intensive agriculture covered 74.3 % of the area but hosted only 23.2 % of the godwit population at low densities (0.063 godwits/ha). In contrast, protected areas (6.2 % of the area) and AES fields (19.5 %) supported 24.7 % and 52.1 % of the population at higher densities (0.48 and 0.46 godwits/ha, respectively). Among AES types, delayed mowing and herb-rich grasslands showed the highest godwit densities (0.66 and 1.25 godwits/ha, respectively) covering smaller areas (6 % and 1.1 %). These AES types pay the highest subsidies, while nest protection, covering 10.5 % of the area with lower godwit densities, pays the lowest. Although AES fields hosted about half of the godwit population, area-wise the focus remained on nest protection, and with intensive agriculture dominated the landscape. This may limit effectiveness at a population level, calling for re-evaluating conservation priorities and funding.